2015
DOI: 10.17509/ijal.v5i1.841
|View full text |Cite
|
Sign up to set email alerts
|

Asean Economic Community 2015: Needs Analysis of Universitas Indonesia’s Engineering Students

Abstract: Prior to the ASEAN Economic Community in the end of 2015, one of the keys for Indonesian engineers to outrank engineers from other ASEAN countries is mastering English language skills. This study aims at analyzing the English needs of undergraduate engineering students at Universitas Indonesia. Questionnaires and semi-structured interviews were used as the data collection methods. The questionnaires were spread to 111 alumni and 150 students from the Faculty of Engineering. The interviews were conducted with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 6 publications
2
12
0
1
Order By: Relevance
“…The finding showed that oral communication was strongly needed by the engineering students at UMM. And this is similar to the findings of Zaid and Kamarudin [39], Kakepoto et al [40], Bhattacharyya [8], Araminta and Halimi [5], Lan, Proust, and Lim, [41].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The finding showed that oral communication was strongly needed by the engineering students at UMM. And this is similar to the findings of Zaid and Kamarudin [39], Kakepoto et al [40], Bhattacharyya [8], Araminta and Halimi [5], Lan, Proust, and Lim, [41].…”
Section: Discussionsupporting
confidence: 91%
“…Also, Aramaninta and Halimi [5], found that the engineering faculty at Universitas Indonesia is enforced to establish English for Professional Purposes handled by both professional English teachers and engineering professionals to meet the needs of engineers in the ASEAN Economic Community. Questionnaires and the interviews were used to collect the data from the alumni, engineering students, the HRD (Human Resources Development) from the local company, head of departments and lecturers.…”
Section: The Role Of Needs Analysis and Course Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…They have more efforts because of learning in a foreign language and have more strategies to be a success. Araminta and Halimi (2015) discuss the limitation of the English skills of the Indonesian workers working in the multinational company, are grammar and pronunciation.…”
Section: Theoretical Framework a The Internationalization Of Higmentioning
confidence: 99%
“…However, policies have been taken to implement EMI (Diallo & Liddicoat, 2014). Araminta and Halimi (2015) reported that from the needs analysis carried out at the Faculty of Engineering at the University of Indonesia, it was concluded that students need a program which can develop their English skills not to teach them English.…”
Section: B Emi In Higher Education In Indonesiamentioning
confidence: 99%